If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 10x = 14x + 5 Reorder the terms: 12 + 10x = 5 + 14x Solving 12 + 10x = 5 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 12 + 10x + -14x = 5 + 14x + -14x Combine like terms: 10x + -14x = -4x 12 + -4x = 5 + 14x + -14x Combine like terms: 14x + -14x = 0 12 + -4x = 5 + 0 12 + -4x = 5 Add '-12' to each side of the equation. 12 + -12 + -4x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 5 + -12 -4x = 5 + -12 Combine like terms: 5 + -12 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75
| 5(a+20)=25 | | -x+(-x+45)=25 | | -5x=7-4x+8 | | -2p^2+70p=0 | | 4(2x+3)=7x+15 | | 24b+3a=0 | | -q-11=2q+14 | | 8a+11=7+15a | | 3a+24b=0 | | 3+12y=6+18y | | -x+(-x+45)=20 | | 9a+7=2+12a | | 10b+8=15b+4 | | 2(3x+4)=5+1 | | 4a-18b=0 | | 6y-9=7y-1 | | 3-x=2.25 | | 6x^2+24x+30=0 | | 2(3X+5)=5X+5 | | 7z+11=0 | | 132=2l+3w | | 10=3z-8 | | 3x-(6-x)=18 | | 5d-2=2d+6 | | 36x=36+121+1 | | t^2-5t+2fort=-4 | | -x=-0.12 | | f(0)=-2x | | 9+11x=107+x | | 4(3x+2)=11+2 | | 4g+1=5g-1-g | | 8x+1=6x+37 |